La historia del análisis económico del derecho en el Perú - Nuñez del Prado , Fabio (2023)
Through this prologue, the author reviews the history of the law and economics in Peru, from its arrival with the help of figures such as Enrique Ghersi or Hernando de Soto, through its dissemination by authors such as Alfredo Bullard, to the practical results that it has had in the country with the creation of INDECOPI or the process of administrative simplification. Likewise, the author develops suggestions that allow consolidating the presence and increasing the efficiency of the law and economics at the national level.